2020
DOI: 10.1111/opo.12714
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis reveals patterns of age‐related change in anterior chamber depth for gender and ethnicity: clinical implications

Abstract: Purpose To identify patterns of age‐, gender‐ and refractive‐ related changes in Scheimpflug‐based anterior chamber depth across the central 8 mm of chamber width, to derive normative models, potentially useful for angle closure disease diagnosis. Methods This was a retrospective, cross‐sectional study. Scheimpflug photography was used to obtain anterior chamber depth measurements at 57 points across the central 8 mm of the chamber width from one eye of each healthy subject (male Caucasians (n = 189), female C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…Various studies had associated shallow anterior chamber and narrow chamber angle with female sex ( 67 69 ). Moreover, females were shown to have greater ACD shallowing with aging than males ( 70 ). The mean ACD values were significantly different from men [2.59 mm (2.56; 2.62)] to women [2.42 mm (2.39; 2.44)] in elderly Chinese (older than 50 years old) ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies had associated shallow anterior chamber and narrow chamber angle with female sex ( 67 69 ). Moreover, females were shown to have greater ACD shallowing with aging than males ( 70 ). The mean ACD values were significantly different from men [2.59 mm (2.56; 2.62)] to women [2.42 mm (2.39; 2.44)] in elderly Chinese (older than 50 years old) ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have demonstrated a poor correlation between gonioscopic angle grading and other quantitative measurements, when evaluating angles that are at the edges of the ordinal gonioscopic scale, i.e., closed/narrow angles and wide-open angles [25,70]. As a consequence, while differentiating between very narrow and wide-open angles may be obvious for the clinician, and consequently highly repeatable, classification of the anatomical continuum between these two extremities into an ordinal gonioscopic scale may be difficult, if not impossible [70,71].…”
Section: Limbal Anterior Chamber Depth Measurement (Lacdm)mentioning
confidence: 99%
“…A major issue with SP and other non-contact imaging techniques (e.g., AS-OCT), is the lack of normative databases, against which the acquired data may be compared. Other than decreasing diagnostic accuracy [71], this may be perceived as a strong limitation, especially by the general clinician in search of clear advice in every-day clinical practice. Building a normative database for these instruments may be challenging.…”
Section: Scheimpflug Photography (Sp)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in reference to the recent article entitled"Cluster analysis reveals patterns of age-related change in anterior chamber depth for gender and ethnicity: clinical implications". 1 We read this article, which deepens understanding of expected changes in anterior chamber depth (ACD), with great interest. The authors mentioned that while skilled gonioscopy is the gold standard for angle evaluation, an objective measurement provided by superior technology such as the rotating Pentacam Scheimpflug camera (Oculus, www.pentacam.com) is not a substitute, but a valuable complementary measurement to complete glaucoma and anterior chamber assessment.…”
Section: To the Editormentioning
confidence: 99%